High-modulus, high-toughness and high-durability composite overhead line system strut and preparation method thereof

By adopting the combined structural design and pultrusion process of high-modulus and high-toughness fiber reinforced composite materials in the railway contact network pillars, the problem of insufficient stiffness of the composite material is solved, and the contact network pillars with high modulus, high toughness and high durability are achieved, meeting the needs of railway applications.

CN119795688APending Publication Date: 2025-04-11RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411931078.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing composite materials have low stiffness in railway contact network pillar applications, making it difficult to meet the needs of high modulus and strength, resulting in the rod body being easily bent or even instable when loaded.

Method used

High-modulus and high-tough fiber reinforced composite materials are used to design the contact web pillars of the hollow structure through a combined structural design method. The outer layer is a high-strength, high-modulus fiber reinforced composite material layer, and the inner layer is a cavity structure layer of high-tough fiber reinforced composite material, and the overall structure is integrated through pultrusion molding process and resin modification technology.

Benefits of technology

It significantly improves the mechanical properties and durability of composite contact network pillars, reduces deflection value, enhances bending resistance, meets the high modulus and high toughness requirements of railway contact network pillars, and reduces transportation costs and operation and maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-modulus, high-toughness and high-durability composite overhead line system strut and a preparation method thereof. An inner and outer layer structure of the catenary strut is designed by adopting a combined structure design method, the outer part is a high-strength high-modulus fiber reinforced composite material layer, and the inner part is a high-toughness fiber reinforced composite material cavity structure layer; the overall structure is integrally formed through a pultrusion process, the synergistic effect of a chain extender is fully played by means of a resin modification technology, and urea bonds are introduced into a resin system, so that the rigidity, toughness, durability and production efficiency of the composite overhead line system strut can be remarkably improved. By spraying the protective layer on the surface, the durability of the contact net strut is ensured, and the contact net strut has remarkable advantages in severe environments such as coastal environments. The preparation technology of the high-modulus, high-toughness and high-durability composite overhead line system supporting column is clear in action mechanism, simple in production process, excellent in performance and suitable for large-scale production, and has important significance on preparation of high-performance composite components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The invention relates to the field of composite material structural parts, and in particular to a composite material contact network support column with high modulus, high toughness and high durability for railway or urban rail transit contact network systems. Background Art

[0004] Composite materials are fiber-reinforced resin composite materials made by winding, pultrusion and other processes using resin as the matrix and glass fiber, carbon fiber, basalt fiber and other reinforcing materials. This type of material has the characteristics of low density, good insulation performance and strong material designability. Using it to manufacture contact network pillars can greatly improve the overall performance of the contact network. It has strong durability and can effectively resist severe corrosion environments such as seawater immersion, saline-alkali environment, heavy pollution and acidic atmosphere; its excellent electrical insulation performance can effectively avoid the risk of lightning strikes, and can greatly reduce or eliminate suspension insulators to improve the wind deflection effect; its low density can greatly reduce the weight of contact network pillars, significantly reduce transportation costs, and increase installation speed; its good durability can greatly reduce operation and maintenance costs, and effectively ensure the safe operation of the contact network. In addition, in terms of comprehensive energy consumption, since the energy consumption and carbon emissions of composite materials in production and manufacturing are far lower than those of the steel and cement industries, they are also more green and environmentally friendly, which is conducive to the implementation of the national dual carbon strategy. In fact, due to the advantages of large breaking bending moment, insulation and lightning protection, and good corrosion resistance, electric poles made of composite materials have been widely used in the power industry in many provinces across the country. As early as 2013, the country's first all-composite electric pole power supply line was built.

[0005] However, there are still obvious technical bottlenecks in applying composite materials to railway contact network pillars. Under normal circumstances, the stiffness of composite materials is relatively low, and it is difficult to fully meet the requirements of use scenarios that require higher modulus and strength. For example, when used in fields such as power grid poles or railway contact network pillars, the deflection value of the current composite material pole under the same load is much larger than that of cement poles and steel structure poles of similar size, about 4 times that of cement poles. This also causes traditional composite material poles to bend significantly when subjected to large lateral forces, and in severe cases even causes the pole to become unstable, making it difficult to meet the requirements for use in related fields.

[0006] Based on the above reasons, the use of high-performance composite materials combined with structural optimization design to develop high-modulus, high-toughness, and high-durability composite contact network pillars has become the research direction of relevant researchers and is also one of the main development directions of composite materials in the future. Patent CN118046627A discloses a method for preparing a bending-resistant and corrosion-resistant composite pole. By combining a polyamide structural layer on the surface of the glass fiber, the strength and toughness of the glass fiber are improved. Patent CN117986845A discloses a method for preparing a lightweight and corrosion-resistant polyurethane composite pole. By optimizing the resin formula and the composite material preparation process, the corrosion resistance of the pole is improved. Patent CN111852154A discloses a method for preparing a high-strength composite pole. By designing a composite material and concrete combined structure, a lightweight, high-strength, corrosion-resistant, and cost-effective composite pole is prepared.

[0007] Since the application conditions of composite materials in contact network pillars are more stringent, and the existing technology pays insufficient attention to the application scenarios of composite materials in contact network pillars, and the research on process and structural design is not sufficient, it cannot meet the application needs of contact network pillars. Therefore, through the coordinated optimization and matching of materials, processes, and structures, the overall performance of composite components can be effectively improved, and composite components with better mechanical properties and durability can be obtained, which is of great significance for the expanded application of composite materials in the engineering field and the further improvement of the industry. Summary of the invention

[0009] The object of the present invention is to solve the above problems and to provide a high modulus, high toughness, high durability composite material contact network support and a preparation method thereof.

[0010] The high modulus, high toughness and high durability composite material contact network pillar structure described in the present invention is a hollow structure, and the outer layer structure is composed of a high-strength and high-modulus fiber-reinforced composite material layer and a high-toughness fiber-reinforced composite material layer; wherein the thickness ratio of the two layers and the cavity part is (0.01~0.03): (0.03~0.09): (0.88~0.96); wherein the fiber-reinforced composite material is a composite material prepared by integrally forming a high modulus polyurethane urea resin and reinforcing fibers in a mass ratio of 1: (2.5~4) through a pultrusion molding process.

[0011] The high modulus polyurethane urea resin in the composite material contact network pillar is composed of component A and component B in a mass ratio of 1: (0.95-1.20).

[0012] The high modulus polyurethane urea resin component A in the composite material contact network pillar is composed of polyol, chain extender, internal mold release agent, catalyst, coupling agent and anti-aging agent. Based on the total mass of component A, the contents of chain extender, internal mold release agent, coupling agent, catalyst and anti-aging agent are 15%-30%, 3%-5%, 0.8%-1.5%, 0.1%-0.8% and 1%-3% respectively; the polyol is composed of one or more of saturated aliphatic polyester polyol, unsaturated aliphatic polyester polyol, polycaprolactone polyol, polyaromatic ester polyol, polymixed acid ester polyol or polyether polyol, with a functionality of 2-4 and a hydroxyl value of 60-480 mgKOH / g; the chain extender is composed of monoethanolamine, 1, 8-octanediamine and propylene glycol are composed together in a mass ratio of (1-3):(0.2-0.5):1; the internal mold release agent is composed of one or more of organic phosphate, zinc stearate, and stearate; the coupling agent is a silane coupling agent; the catalyst is a heat-sensitive delayed catalyst; the anti-aging agent is composed of an ultraviolet absorber, a light stabilizer, and an antioxidant.

[0013] The B component isocyanate in the composite material contact network pillar is composed of one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane dimethylene diisocyanate, p-phenylene diisocyanate, xylene dimethylene diisocyanate, toluene diisocyanate trimer and hexamethylene diisocyanate trimer.

[0014] The high-strength and high-modulus fibers in the composite material contact network support are composed of one or more of carbon fibers, aramid fibers, poly(p-phenylene phthalamide) fibers, aromatic polyamide copolymer fibers, heterocyclic polyamide fibers, or silicon carbide fibers.

[0015] The high-tenacity fibers in the composite material contact network pillar are composed of one or more of glass fibers, basalt fibers, plant fibers, or ultra-high molecular weight polyethylene fibers.

[0016] The cross-sectional shape of the composite material contact network support pillar can be circular, elliptical, square, rectangular or polygonal.

[0017] The length of the composite contact network pillar is 8 m~18 m and can be adjusted according to actual application requirements.

[0018] The preparation method of the composite material contact network pillar comprises the following steps:

[0019] (a) fully dissolving and stirring the polyurethane urea resin component A according to the proportion at 120° C., and cooling to 25° C.;

[0020] (b) arranging the continuous roving or unidirectional fabric of the two parts of fibers in layers according to inner and outer layers;

[0021] (c) continuously drawing a continuous roving or unidirectional cloth of reinforcing fibers through an impregnation chamber and a die;

[0022] (d) continuously feeding the mixture of components A and B of the polyurethane urea resin into the impregnation chamber;

[0023] (e) contacting the reinforcing fibers with the polyurethane urea resin in an impregnation chamber;

[0024] (f) passing the fiber-resin composite material through a mold heated to a fixed temperature to form a cured composite material, wherein the temperatures of the three sections of the mold are 70-100° C., 150-180° C., and 180-210° C. respectively;

[0025] (g) Continuously pulling the composite material out of the mold, with the pulling speed set at 100-300 mm / min;

[0026] (h) Cutting and surface treatment of the cured composite pillars as required.

[0027] The surface treatment in step (h) of the preparation method includes polishing, painting or coating a protective layer.

[0028] The positive effects of the high modulus, high toughness, and high durability composite material contact network support and the preparation method thereof of the present invention are:

[0029] (1) The present invention adopts a combined structural design method to design the inner and outer layer structures of the contact network pillar. The outer layer is a high-strength and high-modulus fiber-reinforced composite material layer, which provides strength and modulus improvements for the composite contact network pillar and ensures good durability of the composite material; the inner layer is a high-toughness fiber-reinforced composite material cavity structure layer, which provides toughness improvements for the composite contact network pillar through specific fiber weaving technology, and can effectively prevent local instability of the composite contact network pillar. Through the design of the inner and outer layer structures, the mechanical and durability performance of the composite contact network pillar can be synergistically improved.

[0030] (2) The present invention introduces urea bonds by adding amine chain extenders to traditional polyurethane resins, and constructs a cross-linked network by combining triol cross-linkers, giving full play to the synergistic effect of chain extenders, while improving the mechanical properties of the resin, achieving precise control of its viscosity and reaction time, thereby ensuring good process performance of the resin. Coupling agents are added to the resin to improve the wetting and bonding effect between the resin and the fiber. In addition, the optimized design of the anti-aging additive system in the resin has a positive effect on ensuring the durability of the pillar.

[0031] (3) The present invention uses a pultrusion process to form the overall structure in one piece, and uses resin modification technology to facilitate good bonding between layers, and can significantly improve the mechanical properties, durability and production efficiency of the composite material contact network pillar.

[0032] (4) While meeting the designed working conditions, the present invention significantly reduces the weight of the contact network pillars, making them easier to transport over long distances and on-site. In mountainous areas, they can be manually carried up the mountain, reducing the difficulty of transportation. By spraying a protective layer on the surface, the durability of the contact network pillars is ensured, which has significant advantages in harsh environments such as coastal areas, thereby extending the service life of the composite material contact network pillars and ensuring their safety in use.

[0033] It can be seen that the high modulus, high toughness, and high durability composite contact network support provided by the present invention has a clear mechanism of action, a simple production process, and excellent performance, is suitable for large-scale production applications, and is of great significance for the preparation of high-performance composite components. DETAILED DESCRIPTION

[0035] The present invention is further described in detail below with reference to specific embodiments.

[0036] Embodiment 1:

[0037] (1) Polyurethane urea resin composition: Component A: 34 kg polyoxypropylene triol (MN-500), 8.3 kg monoethanolamine, 2.1 kg 1, 8-octanediamine, 4.2 kg propylene glycol, 2 kg internal release agent (Axel INT 1960MCH), 0.08 kg catalyst (Evonik SA-8), 0.5 kg silane coupling agent (KH550), 0.5 kg ultraviolet absorber (UV-329), 0.5 kg light stabilizer (770), 0.5 kg antioxidant (245); Component B: 53 kg modified diphenylmethane diisocyanate (WANNATE PM-8212).

[0038] (2) Fully dissolve and stir the polyurethane urea resin component A at 120°C, evacuate under a negative pressure of 0.1 MPa for 2 to 3 h to completely remove residual moisture, and cool to 25°C;

[0039] (3) The outer fiber of each side of the pillar is made of 15 layers with a weight of 300 g / m 2 The carbon fiber unidirectional cloth, the inner layer fiber uses 110 9600tex high-strength glass fiber untwisted rovings, arranged in layers according to the inner and outer layers;

[0040] (4) The polyurethane urea resin components A and B were mixed and injected into the mold impregnation chamber using a two-component glue injection machine. The temperatures of the three sections of the mold were set to 80 °C, 160 °C, and 190 °C, respectively. The composite material was continuously pulled out of the mold at a pulling speed of 200 mm / min.

[0041] (5) Cutting and surface treatment of the composite material pillar after solidification to obtain a composite material contact network pillar with high modulus, high toughness and high durability.

[0042] Embodiment 2:

[0043] (1) Polyurethane urea resin composition: Component A: 42 kg polycaprolactone diol (PLACCEL 205U), 6.0 kg monoethanolamine, 1.3 kg 1, 8-octanediamine, 6.5 kg propylene glycol, 2.5 kg internal release agent (Axel INT 1948MCH), 0.15 kg catalyst (Evonik K-16), 0.7 kg silane coupling agent (KH570), 0.6 kg ultraviolet absorber (UV-320), 0.5 kg light stabilizer (622), 0.4 kg antioxidant (1010); Component B: 60 kg polymethylene polyphenyl isocyanate (WANNATE PM-200).

[0044] (2) Fully dissolve and stir the polyurethane urea resin component A at 120°C, evacuate under a negative pressure of 0.1 MPa for 2 to 3 h to completely remove residual moisture, and cool to 25°C;

[0045] (3) The outer fiber of each side of the pillar is made of 18 layers with a weight of 300 g / m 2 The carbon fiber unidirectional cloth, the inner layer fiber uses 90 9600tex high-strength glass fiber untwisted rovings, arranged in layers according to the inner and outer layers;

[0046] (4) The polyurethane urea resin components A and B were mixed and injected into the mold impregnation chamber using a two-component glue injection machine. The temperatures of the three sections of the mold were set to 70°C, 150°C, and 180°C, respectively. The composite material was continuously pulled out of the mold at a pulling speed of 180 mm / min.

[0047] (5) Cutting and surface treatment of the composite material pillar after solidification to obtain a composite material contact network pillar with high modulus, high toughness and high durability.

[0048] Embodiment 3:

[0049] The same as Example 1, the only difference is the selection of inner and outer fiber layers. The outer fiber of each side is 20 layers with a weight of 240 g / m 2 The aramid fiber unidirectional cloth has 215 4800tex high-strength basalt fiber rovings as the inner fiber.

[0050] Embodiment 4:

[0051] It is basically the same as Example 2, except that the only difference is the selection of the inner and outer layer fibers. The outer layer fibers on each side are 25 layers with a gram weight of 240 g / m 2 The aramid fiber unidirectional cloth has 160 4800tex high-strength basalt fiber rovings as the inner fiber.

[0052] Comparative Example 1:

[0053] The method is basically the same as Example 1, except that the resin composition adopts commercially available polyurethane resin for pultrusion molding: component A: WANEFLEX 650N, component B: WANNATE 82681.

[0054] Comparative Example 2:

[0055] It is basically the same as Example 2, except that the resin composition adopts commercially available polyurethane resin for pultrusion molding: component A: Baydur 18BD228, component B: Desmodur 1511L.

[0056] Comparative Example 3:

[0057] It is basically the same as Example 1, the only difference is the difference in the resin composition, which is specifically shown below.

[0058] Polyurethane urea resin combination: Component A: 34kg polyoxypropylene triol (MN-500), 14.6kg propylene glycol, 2kg internal release agent (Axel INT 1960MCH), 0.08kg catalyst (Evonik SA-8), 0.5kg silane coupling agent (KH550), 0.5kg ultraviolet absorber (UV-329), 0.5kg light stabilizer (770), 0.5kg antioxidant (245); Component B: 64kg modified diphenylmethane diisocyanate (WANNATE PM-8212).

[0059] Comparative Example 4:

[0060] It is basically the same as Example 2, the only difference is the difference in the resin composition, which is specifically shown below.

[0061] Polyurethane urea resin combination: Component A: 42kg polycaprolactone diol (PLACCEL 205U), 14.6kg monoethanolamine, 2.5kg internal release agent (Axel INT 1948MCH), 0.15kg catalyst (Evonik K-16), 0.7kg silane coupling agent (KH570), 0.6kg ultraviolet absorber (UV-320), 0.5kg light stabilizer (622), 0.4kg antioxidant (1010); Component B: 52kg polymethylene polyphenyl isocyanate (WANNATE PM-200).

[0062] Comparative Example 5:

[0063] It is basically the same as Example 2, the only difference is the difference in the resin composition, which is specifically shown below.

[0064] Polyurethane urea resin combination: Component A: 42kg polycaprolactone diol (PLACCEL 205U), 14.6kg 1, 8-octanediamine, 2.5kg internal release agent (Axel INT 1948MCH), 0.15kg catalyst (Evonik K-16), 0.7kg silane coupling agent (KH570), 0.6kg ultraviolet absorber (UV-320), 0.5kg light stabilizer (622), 0.4kg antioxidant (1010); Component B: 48kg polymethylene polyphenyl isocyanate (WANNATE PM-200).

[0065] Comparative Example 6:

[0066] It is basically the same as Example 1, the only difference is the difference in the resin composition, which is specifically shown below.

[0067] Polyurethane urea resin combination: Component A: 34kg polyoxypropylene triol (MN-500), 7.0kg monoethanolamine, 7.6kg propylene glycol, 2kg internal release agent (Axel INT 1960MCH), 0.08kg catalyst (Evonik SA-8), 0.5kg silane coupling agent (KH550), 0.5kg ultraviolet absorber (UV-329), 0.5kg light stabilizer (770), 0.5kg antioxidant (245); Component B: 62kg modified diphenylmethane diisocyanate (WANNATE PM-8212).

[0068] Comparative Example 7:

[0069] It is basically the same as Example 2, the only difference is the difference in the resin composition, which is specifically shown below.

[0070] Polyurethane urea resin combination: Component A: 42kg polycaprolactone diol (PLACCEL 205U), 7.0kg 1, 8-octanediamine, 7.6kg monoethanolamine, 2.5kg internal release agent (Axel INT 1948MCH), 0.15kg catalyst (Evonik K-16), 0.7kg silane coupling agent (KH570), 0.6kg ultraviolet absorber (UV-320), 0.5kg light stabilizer (622), 0.4kg antioxidant (1010); Component B: 50kg polymethylene polyphenyl isocyanate (WANNATE PM-200).

[0071] Comparative Example 8:

[0072] It is basically the same as Example 1, the only difference is the difference in the pillar structure layer. The inner and outer layer fibers of each side are made of 9600tex high-strength glass fiber untwisted roving, with a total of 235 fibers.

[0073] Comparative Example 9:

[0074] It is basically the same as Example 2, except that the only difference is the difference in the pillar structure layer. The inner and outer layers of each side are made of 300 g / m 2 Carbon fiber unidirectional cloth, a total of 36 layers.

[0075] Effect description:

[0076] Composite contact network pillars of the same specifications were prepared according to Examples 1 to 4 and Comparative Examples 1 to 6, wherein the pillars were in the shape of square tubes with a length of 8 m, a cross-sectional side length of 300 mm, a wall thickness of 10 mm, and a capacity of 60 kN·m. Performance tests were performed and compared under the same conditions.

[0077] Samples were taken from the composite material contact network pillars and tested for mechanical properties and durability. The longitudinal tensile properties, compression properties, bending properties and impact toughness were tested according to GB / T 1447-2005, GB / T 1448-2005, GB / T 1449-2005 and GB / T 1451-2005 respectively. The UV aging test simulated the natural UV aging effect of the product according to GB / T 16422.3-2022, using a type 2 (UVB-313) lamp (method C), and the exposure cycle was 1000h. The salt spray aging was carried out according to the neutral salt spray test (NSS) method specified in GB / T10125-2021, and the aging was 1000h. The wet heat aging: according to the wet heat test method specified in GB / T 2573-2008, the aging was 720h. In addition, the column top deflection test of the composite material contact network pillar was carried out according to TB / T 2286-2020. The results are shown in Table 1.

[0078] Table 1 Performance of composite contact network pillars prepared in Examples 1 to 4 and Comparative Examples 1 to 6

[0079] sample Longitudinal tensile strength (MPa) Longitudinal compressive strength (MPa) Longitudinal bending strength (MPa) Longitudinal bending elastic modulus (GPa) <![CDATA[Impact toughness (kJ / m 2 )]]> UV aging bending strength retention rate (%) Salt spray aging flexural strength retention rate (%) Retention rate of flexural strength after wet heat aging (%) Pillar top deflection (mm) Example 1 1567 1343 1589 66.4 928 96.4 97.2 95.5 93.5 Example 2 1502 1285 1556 63.3 901 95.3 96.8 94.2 96.2 Example 3 1524 1305 1604 61.1 994 94.9 97.5 93.8 103.2 Example 4 1577 1299 1592 59.5 1024 96.2 98.2 94.0 102.7 Comparative Example 1 1265 1137 1301 48.5 662 86.9 92.3 88.7 125.2 Comparative Example 2 1293 1188 1376 52.3 721 87.5 91.1 89.3 121.5 Comparative Example 3 1201 1101 1282 48.3 602 86.3 90.5 88.2 128.5 Comparative Example 4 1172 1082 1223 47.4 593 87.1 90.1 89.2 126.3 Comparative Example 5 1189 1136 1266 47.2 651 88.5 87.6 90.2 125.7 Comparative Example 6 1322 1205 1398 54.6 756 90.2 93.2 91.6 120.1 Comparative Example 7 1356 1212 1305 52.3 801 91.4 92.6 90.8 122.2 Comparative Example 8 1354 1152 1325 49.2 775 87.5 90.1 90.3 131.6 Comparative Example 9 1172 1056 1186 55.2 802 88.6 91.6 89.2 128.4

[0080] It can be seen from the data in Table 1 that the polyurethane composite material contact network pillar materials prepared in Examples 1 to 4 have excellent mechanical properties and durability, high strength, modulus and toughness, and still have a bending strength retention rate of more than 90% after UV, salt spray, and wet heat aging. In addition, the overall stiffness of the composite material contact network pillar prepared in the example is large, and the column top deflection can be controlled within the deflection limit of 120mm (1.5% of the pillar height) of the railway contact network pillar. This effectively verifies the feasibility of the application of polyurethane composite material contact network pillars in railways.

[0081] Comparative Examples 1 and 2 use commercially available polyurethane resin composite materials to prepare composite contact network pillars. Since there is no urea bond introduced into the polyurethane resin structure, the mechanical properties of the resin body are relatively low, and the bonding performance with the fiber interface is relatively poor, the transmission of fracture stress and microcracks and interface slip are easy, and the mechanical properties of the composite material are lower than those of the embodiment. In addition, since the anti-aging additive system is not optimized, the bending strength retention rate of the composite material after aging is relatively low. These factors lead to insufficient rigidity of the finished composite contact network pillar, and the column top deflection exceeds the deflection limit of 120mm, which poses a safety hazard in long-term use.

[0082] The resin systems of Comparative Examples 3, 4 and 5 use only a single chain extender, the material properties are poor, and the pillar deflection exceeds the limit. The resin systems of Comparative Examples 6 and 7 use only 1, 8-octanediamine or monoethanolamine and propylene glycol as chain extenders. Compared with the case of using only propylene glycol as a chain extender (Comparative Example 3), the mechanical properties of the composite material are slightly improved, with the maximum improvement reaching about 10%, but the chain extension and cross-linking effects of the chain extender cannot be fully utilized, and the material properties are still insufficient, resulting in the pillar deflection only decreasing by about 6.5%, which is still beyond the limit.

[0083] When diamines with different rigid structures (monoethanolamine and 1,8-octanediamine) are compounded with propylene glycol in a certain proportion, the mechanical properties of the composite material are improved by more than 30% and the pillar deflection is reduced by 27% compared with the case where only propylene glycol is used as a chain extender (Comparative Example 3). This shows that different types of chain extenders show a significant synergistic effect, thereby achieving a synergistic improvement in the stiffness, toughness and working performance of the resin system and the composite material, and the stiffness of the prepared pillar is significantly improved. It can be seen from Comparative Examples 8 and 9 that the fiber structure design of the inner and outer layers of the pillar plays a key role in the overall performance of the pillar. The use of high-strength high-modulus fiber or high-toughness fiber alone will lead to insufficient overall mechanical properties of the composite material, resulting in the pillar top deflection unable to meet the use requirements.

[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A high modulus, high toughness, high durability composite material contact network support and a preparation method thereof, characterized in that: The contact network pillar structure is a hollow structure, and the outer layer structure is composed of a high-strength and high-modulus fiber-reinforced composite material layer and a high-toughness fiber-reinforced composite material layer; wherein the thickness ratio of the two layers and the cavity part is (0.01~0.03): (0.03~0.09): (0.88~0.96); wherein the fiber-reinforced composite material is a composite material prepared by integrally forming a high-modulus polyurethane urea resin and reinforcing fibers in a mass ratio of 1: (2.5~4) through a pultrusion molding process.

2. A high modulus, high toughness, high durability composite material contact network support and its preparation method according to claim 1, characterized in that: The high modulus polyurethane urea resin is composed of component A and component B in a mass ratio of 1:(0.95-1.20).

3. A high modulus, high toughness, high durability composite material contact network support and its preparation method according to claim 2, characterized in that: The high modulus polyurethane urea resin component A is composed of polyols, chain extenders, internal mold release agents, catalysts, coupling agents and anti-aging agents. Based on the total mass of component A, the contents of the chain extenders, internal mold release agents, coupling agents, catalysts and anti-aging agents are 15% to 30%, 3% to 5%, 0.8% to 1.5%, 0.1% to 0.8% and 1% to 3%, respectively. The polyol is composed of one or more of saturated aliphatic polyester polyols, unsaturated aliphatic polyester polyols, polycaprolactone polyols, polyaromatic ester polyols, polyester polyols or polyether polyols, with a functionality of 2 to 4 and a hydroxyl value of 60 to 480 mgKOH / g. The chain extender is composed of monoethanolamine, 1, 8-octanediamine and propylene glycol are composed together in a mass ratio of (1-3):(0.2-0.5):1; the internal mold release agent is composed of one or more of organic phosphate, zinc stearate, and stearate; the coupling agent is a silane coupling agent; the catalyst is a heat-sensitive delayed catalyst; the anti-aging agent is composed of an ultraviolet absorber, a light stabilizer, and an antioxidant.

4. A high modulus, high toughness, high durability composite material contact network support and its preparation method according to claim 2, characterized in that: The high modulus polyurethane urea resin B component isocyanate is composed of one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane dimethylene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, toluene diisocyanate trimer and hexamethylene diisocyanate trimer.

5. A high modulus, high toughness, high durability composite material contact network support and its preparation method according to claim 1, characterized in that: The high-strength and high-modulus fiber is composed of one or more of carbon fiber, aramid fiber, poly(p-phenylene terephthalamide) fiber, aromatic polyamide copolymer fiber, heterocyclic polyamide fiber, or silicon carbide fiber.

6. A high modulus, high toughness, high durability composite material contact network support and its preparation method according to claim 1, characterized in that: The high-tenacity fiber is composed of one or more of glass fiber, basalt fiber, plant fiber, or ultra-high molecular weight polyethylene fiber.

7. A high modulus, high toughness, high durability composite material contact network support and a preparation method thereof according to claim 1, characterized in that: The cross-sectional shape of the pillar may be circular, elliptical, square, rectangular or polygonal.

8. A high modulus, high toughness, high durability composite material contact network support and a preparation method thereof according to claim 1, characterized in that: The length of the pillar is 8 m to 18 m.

9. A high modulus, high toughness, high durability composite material contact network support and a preparation method thereof according to claim 1, characterized in that: The preparation method of the composite material contact network pillar comprises the following steps: (a) fully dissolving and stirring the polyurethane urea resin component A according to the proportion at 120° C., and cooling to 25° C.; (b) arranging the continuous roving or unidirectional fabric of the two parts of fibers in layers according to inner and outer layers; (c) continuously drawing a continuous roving or unidirectional cloth of reinforcing fibers through an impregnation chamber and a die; (d) continuously feeding the mixture of components A and B of the polyurethane urea resin into the impregnation chamber; (e) contacting the reinforcing fibers with the polyurethane urea resin in an impregnation chamber; (f) passing the fiber-resin composite material through a mold heated to a fixed temperature to form a cured composite material, wherein the temperatures of the three sections of the mold are 70-100° C., 150-180° C., and 180-210° C. respectively; (g) Continuously pulling the composite material out of the mold, with the pulling speed set at 100-300 mm / min; (h) Cutting and surface treatment of the cured composite pillars as required.

10. A high modulus, high toughness, high durability composite material contact network support and a preparation method thereof according to claim 9, characterized in that: The surface treatment includes polishing, painting or applying a protective layer.

Citation Information

Patent Citations

  • High-strength composite electric pole

    CN111852154A

  • Light polyurethane composite electric pole with good corrosion resistance and preparation method thereof

    CN117986845A

  • Bending-resistant corrosion-resistant composite material electric pole and preparation method thereof

    CN118046627A

  • Large-scale composite material wind-power blade and preparation method thereof

    CN101705922A

  • Hydroxyl-containing bis-secondary amine as well as preparation method and application thereof

    CN115215755A